Employers, the government, and industrial fatigue in Britain, 1890-1918. - McIvor, A J (1987)
The evolution of the concept of industrial fatigue and the responses of employers and the government in Britain to research initiatives in this field of industrial medicine up to the end of the first world war is explored. The discussion dovetails in with the broader debate about the characteristics and dissemination of scientific labour management in Britain. The first section focuses on attitudes towards human energy expenditure and overwork in the nineteenth century. Following this is a discussion of the shorter hours movement of the 1890s, the important experiment at the Manchester engineering firm of Mather and Platt, and the reaction of British employers and the government to this. Finally, a brief analysis is made of the progress in research into workers' health, fatigue, and efficiency during the 1914-8 war, particularly concentrating on the role of the Health and Munition Workers Committee in pioneering the scientific study of industrial medicine. This led directly to the establishment of the Industrial Fatigue Research Board in 1918. Though there are significant caveats, it is argued that before the first world war a wide gap existed between research findings, best practice, and the common workshop experience and that in general British management (with some notable exceptions) grossly neglected the human element in production, ignored human physiological and psychological limitations, and hence both created and exacerbated serious problems of mental and physical fatigue and overstrain.